Pengaruh Financial Socialization dan Financial Experience terhadap Investment Intention Melalui Financial Literacy Sebagai Mediasi pada Karyawan Swasta Kota Cikarang - Rahimah Saleh (Syntax Idea, 1923)
This research aims to investigate the influence of two key factors, namely Financial Socialization and Financial Experience, on the investment intention of private sector employees in the city of Cikarang. Additionally, this study also analyzes the role of Financial Literacy as a mediator in the relationship between Financial Socialization, Financial Experience, and Investment Intention. The research methodology employs a quantitative approach with data collection through questionnaires distributed to private sector employees in Cikarang. Data analysis is conducted using regression techniques and mediation analysis. The research findings indicate that Financial Socialization and Financial Experience have a significant influence on Investment Intention. Furthermore, Financial Literacy has been proven to mediate the relationship between Financial Socialization, Financial Experience, and Investment Intention. These findings have important implications for human resources practitioners and educational institutions to enhance financial understanding and investment intentions among private sector employees in Cikarang. Moreover, this research also provides a strong theoretical foundation for further studies in the fields of financial literacy and financial behavior of employees.